Mammalian CDC14 phosphatases control exit from stemness in pluripotent cells. (3rd November 2022) - Villarroya‐Beltri, Carolina; Martins, Ana Filipa B; García, Alejandro; Giménez, Daniel; Zarzuela, Eduardo; Novo, Mónica; del Álamo, Cristina; González‐Martínez, José; Bonel‐Pérez, Gloria C; Díaz, Irene; Guillamot, María; Chiesa, Massimo; et al.
Abstract: Maintenance of stemness is tightly linked to cell cycle regulation through protein phosphorylation by cyclin‐dependent kinases (CDKs). However, how this process is reversed during differentiation is unknown. We report here that exit from stemness and differentiation of pluripotent cells along the neural lineage are controlled by CDC14, a CDK‐counteracting phosphatase whose function in mammals remains obscure. Lack of the two CDC14 family members, CDC14A and CDC14B, results in deficient development of the neural system in the mouse and impairs neural differentiation from embryonic stem cells (ESCs). Mechanistically, CDC14 directly dephosphorylates specific proline‐directed Ser/Thr residues of undifferentiated embryonic transcription Factor 1 (UTF1) during the exit from stemness, triggering its proteasome‐dependent degradation. Multiomic single‐cell analysis of transcription and chromatin accessibility in differentiating ESCs suggests that increased UTF1 levels in the absence of CDC14 prevent the proper firing of bivalent promoters required for differentiation. CDC14 phosphatases are dispensable for mitotic exit, suggesting that CDC14 phosphatases have evolved to control stemness rather than cell cycle exit and establish the CDK‐CDC14 axis as a critical molecular switch for linking cell cycle regulation and self‐renewal. Synopsis: CDC14 phosphatases play critical roles in counteracting cell cycle kinases during mitotic exit in yeast. New data in mouse models suggest that mammalian CDC14 has evolved to regulate stemness exit in progenitor cells during differentiation. Lack of both murine CDC14A and CDC14B results in perinatal lethality, accompanied by defective development of the neural system. CDC14‐deficient embryonic stem cells show normal cell cycle exit and proliferation but display impaired neural differentiation. CDC14 phosphatases dephosphorylate the epigenetic regulator UTF1 and induce its degradation during the exit of stemness. UTF1 destabilization by CDC14 is accompanied by the de‐repression of bivalent promoters required for neural cell differentiation. Abstract : While yeast CDC14 has critical roles in mitotic exit, loss of mouse CDC14A/B does not affect proliferation, but neural differentiation via the epigenetic regulator UTF1.